Competition between pinning produced by extrinsic random point disorder and superconducting thermal fluctuations in oxygen-deficient GdBa2Cu3Ox coated conductors - Haberkorn, Nestor Fabian (2019)
We report on the influence of random point defects introduced by 3 MeV proton irradiation on the vortex dynamics of 1.3 μm thick GdBa2Cu3Ox coated conductors. Thin films with different oxygen stoichiometry (6.7 < × < 7) were irradiated with 3 MeV proton (p) using a fluence of 2 × 1016 p cm−2. We find a direct correlation between the changes in Tc produced by oxygen content and damage by irradiation on the resulting vortex dynamics in the films. The analysis of the critical current densities Jc at low temperatures indicates that although irradiation produces smooth magnetic field dependences, the self-field values decrease systematically as Tc reduces. Moreover, the analysis of the relaxation of the persistent currents shows that the characteristic glassy exponent μ systematically decreases from 1.7 to 0.66 as Tc decreases from 93 to 55 K.